2018
DOI: 10.1371/journal.pone.0192646
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of inner retinal layers as biomarkers in mild cognitive impairment to moderate Alzheimer’s disease

Abstract: Inner retina in Alzheimer's Disease (AD) may experience neuroinflammation resulting in atrophy. The objective of our study was to determine whether retinal GCIPL (ganglion cell-inner plexiform layer) or nerve fiber layer (NFL) thickness may serve as noninvasive biomarkers to diagnose AD. This cross-sectional case-control study enrolled 15 mild cognitive impairment (MCI) patients, 15 mild-moderate AD patients, and 18 cognitively normal adults. NFL and GCIPL thicknesses on optical coherence tomography (OCT) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(147 citation statements)
references
References 64 publications
4
139
1
3
Order By: Relevance
“…It may be argued that this anatomic fact makes neuronal loss in MCI and AD easier to detect with OCT. Matching our findings, Lad et al [36] found a reduction in GC-IPL thickness in the inner sector of patients with MCI. In a previous study on patients with AD conducted by our group [25], full macular thickness was preferentially affected in a 3-mm circle around the fovea, suggesting that MCI and AD have similar patterns of ganglion cell impairment and, consequently, supporting the notion that MCI and AD are part of the same spectrum of neurodegeneration.…”
Section: Discussionsupporting
confidence: 91%
“…It may be argued that this anatomic fact makes neuronal loss in MCI and AD easier to detect with OCT. Matching our findings, Lad et al [36] found a reduction in GC-IPL thickness in the inner sector of patients with MCI. In a previous study on patients with AD conducted by our group [25], full macular thickness was preferentially affected in a 3-mm circle around the fovea, suggesting that MCI and AD have similar patterns of ganglion cell impairment and, consequently, supporting the notion that MCI and AD are part of the same spectrum of neurodegeneration.…”
Section: Discussionsupporting
confidence: 91%
“…Our results reflect these findings, as we found significant GCL thinning in the four sectors. On the contrary, some in vivo studies displayed controversial GCL measurements using SD-OCT, reporting that RNFL and GCL thickness were unable to distinguish AD dementia from MCI and normal controls in clinically well-characterized series [37,38]. The authors themselves hypothesized that a larger series would be necessary to delineate significant differences between the groups studied.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study made by Correa-Jaraba and colleagues confirmed that the event-related potential technique is useful for evaluating changes in brain electrical activity and increased amplitude of the P3a component is a novel neurocognitive marker for differentiating amnestic MCI [35].…”
Section: Genetic Typesmentioning
confidence: 96%